Effects of the neurokinin-1 antagonist maropitant on canine gastric emptying assessed by radioscintigraphy and breath test - Schmitz, Silke; Fink, Tamara; Failing, Klaus; Borsch, Christian; Kunz, Clemens; Clemence, Richard; Savary-Bataille, Karine; Neiger, Reto (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2016)
Objective: Delayed gastric emptying is a well-recognised phenomenon in a number of canine disease conditions. Only a limited number of drugs have been reported to have some gastrokinetic effect in the dog. The aim of this study was to investigate prokinetic effects of maropitant. Material and methods: In a cross-over study 24 healthy adult Beagle dogs were randomised to receive either maropitant (2 mg/kg q24 h PO), cisapride (1 mg/kg q12 h PO) or placebo (vitamin- B12, 10 μg/dog q24 h PO) for 7 days with a 7-day washout period between treatments. Gastric emptying was measured simultaneously via 99mTechnetium radioscintigraphy and 13C-sodium acetate breath testing for 6 hours post-feeding. The decrease in radioactive counts in the stomach and the increase in 13CO2 concentration in exhaled breath (measured via gas chromatography) were plotted against time. The area under the curve was determined for each test and the time to 25%, 50% and 75% gastric emptying was calculated for each method. Friedman test was used to compare gastric emptying times. Results: With both methods, no difference for gastric emptying times was observed for any treatment. Conclusion and clinical relevance: Neither maropitant nor cisapride were shown to have an effect on gastric emptying in healthy beagles using radioscintigraphy or breath test when compared to placebo. Consequently, neither drug can be recommended as a gastric prokinetic in dogs.
Keywords: Stomach; motility; dog; prokinetic; cisapride